Streetscape Features Related to Pedestrian Activity - Ewing, R.; Hajrasouliha, A.; Neckerman, K.; Purciel-Hill, M.; Greene, William (Sage Publications, 2016)
By measuring twenty streetscape features and numerous other variables for 588 blocks in New York City, we were able to identify variables that explain pedestrian traffic volumes. We found significant positive correlations between three out of twenty streetscape features with pedestrian counts after controlling for density and other built environmental variables. The significant streetscape features are the proportion of windows on the street, the proportion of active street frontage, and the number of pieces of street furniture. This study provides guidance for streetscape projects that aim to create walkable streets and pedestrian-friendly environments.